Protective effects of YCHD on the autoimmune hepatitis mice model induced by Ad-CYP2D6 through modulating the Th1/Treg ratio and intestinal flora - Wu, Jiawen; Lyu, Sixue; Guo, Di; Yang, Na; Liu, Yang (Frontiers in Immunology, 2024)
Background: Autoimmune hepatitis (AIH) is a chronic liver inflammatory disease mediated by autoimmune reactions, the pathogenesis of AIH is probably related to the imbalance of intestinal flora. Yinchenhao decoction (YCHD) has been used to relieve AIH. However, the mechanisms underpinning YCHD's hepatoprotective effects with the gut microbito have not been fully revealed.Objective: To explore the potential mechanism of YCHD in treating AIH based on changes in the intestinal flora and Th1/Treg ratio in the spleen and hepatic hilar lymph nodes.The AIH mice model induced by the adenovirus vectors that overexpress human cytochrome P450 family 2 subfamily D member 6 (Ad-CYP2D6) was established (untreated group). One week after the Ad-CYP2D6 injection, the AIH model mice were treated by administering YCHD by gavage for 14 days (YCHD-treated group). The therapeutic efficacy of YCHD on AIH was evaluated by detecting the histopathological changes of the liver, serum transaminases (ALT and AST), inflammatory factors (TNF-α、IL-17 and IFN-γ), and autoantibodies (including LKM-1 and LC-1). The ratio of Th1 to Treg within the spleen and hepatic hilar lymph nodes of the mice was detected by flow cytometry. The changes in the species and abundance of intestinal flora and intestinal flora metabolites were analyzed via 16S rRNA gene sequencing and gas chromatography-mass spectrometry (GC/MS) to reveal the protective mechanism of YCHD on liver injury.Result: YCHD decreased the transaminase activity (AST and ALT), the content of autoantibodies (LC-1 and LKM-1), and the serum TNF-α, IL-12, and IL-17 levels in AIH mice. The degree of inflammatory infiltration in the YCHD-treated group was significantly less than that in the untreated group. YCHD can effectively reverse the abundance and diversity of intestinal flora in AIH mice and affect the release of short-chain fatty acids (SCFAs), especially butyric acid. Moreover, the flow cytometry results showed that YCHD could also decline the ratio of Th1/Treg, which probably be induced by SCFAs via the G protein-coupled receptor (GPR).YCHD may affect the release of SCFAs by regulating the intestinal microbiota, thereby affecting the differentiation of Th1 and Treg, and achieving the effect of alleviating liver damage.